Persepsi dan Preferensi Masyarakat Terkait Dampak Reklamasi Pantai Pasca Pembangunan Labuan Bajo - Rukmana, Siti Nuurlaily; Jehamat, Iluminata Lafaniati; Sucipto, Sucipto (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Reclamation of Labuan Bajo Beach provides various options, including the provision of land in the region/city, development of coastal tourism and business activity centres, arrangement of integrated transportation systems, improving the quality and economic value of coastal areas, and contribution to the economy for the region and the community both APBD and new jobs. This study aims to analyse public perceptions and preferences regarding the impact of beach reclamation post-construction of the Labuan Bajo KSPN, West Manggarai Regency. Methods of data collection using a questionnaire. The data analysis technique uses Importance Performance Analysis (IPA). The results of community perceptions and preferences are in quadrant II, which means that people think that the reclamation of Labuan Bajo Beach has a positive impact or deserves to be maintained its superiority. Some items worth keeping include increasing income, supporting the economy, opening up employment opportunities, changing land functions, and changing coastlines